Pelatihan Code Blue System dan Penggunaan Automated External Defibrilator (AED) bagi Perawat Puskesmas - Kustanti, Cecilya; Widyarani, Linda (Universitas Malahayati Lampung, 2024)
ABSTRAK Initial assessment pada kasus kegawatdaruratan sistem kardiovaskuler di puskesmas harus dilakukan dengan cepat dan tepat. Perawat sebagai salah satu petugas kesehatan harus mempunyai kompetensi dalam penatalaksanaan kasus kegawatdaruratan sistem kardiovaskuler. Salah satu kompetensi yang harus dimiliki adalah aktivasi code blue system dan penggunaan AED (Automated External Defibrillator), kompetensi tersebut diharapkan sebagai upaya peningkatan ketahanan pelayanan kesehatan di IGD puskesmas pada kasus kegawatdaruratan sistem kardiovaskuler. Tujuan kegiatan pengabdian kepada masyarakat ini adalah meningkatkan pengetahuan perawat yang bekerja di IGD puskesmas, tentang aktivasi code blue system dan penggunaan AED dalam penanganan pasien dengan kegawatdaruratan jantung di puskesmas. Kegiatan pengabdian kepada masyarakat ini dilakukan di Dinas Kesehatan, Kabupaten Bantul, Provinsi Daerah Istimewa Yogyakarta. Hasil dari kegiatan pengabdian kepada masyarakat ini, terdapat peningkatan pengetahuan perawat yang bekerja di IGD tentang aktivasi code blue system dan penggunaan AED dalam penanganan pasien dengan kegawatdaruratan jantung di puskesmas, meningkat dari 64,60±4,65 menjadi 83,08±2,26. Kata Kunci: Code Blue System, Automated External Defibrilator, Perawat ABSTRACT Initial assessments in cases of cardiovascular system emergencies at community health centers must be carried out quickly and accurately. As healthcare professionals, nurses need to be proficient in handling cardiovascular emergency patients. One of the necessary skills is knowing how to operate an Automated External Defibrillator (AED) and activate the code blue system. These competences are anticipated to be an attempt to improve the resiliency of medical services in the event of cardiovascular system problems at the health center's emergency department. The purpose of this community service project is to raise the level of awareness among the nurses who staff the community health center's emergency department on how to activate the code blue system and how to utilize AEDs when treating patients experiencing cardiac crises. The Health Service in Bantul Regency, Yogyakarta Special Region Province, was the site of this community service project. This community service activity was carried out at the Health Service, Bantul Regency, Yogyakarta Special Region Province. As a result of this community service activity, there was an increase in the knowledge of nurses working in the emergency room regarding activation of the code blue system and the use of AEDs in treating patients with cardiac emergencies at community health centers, increasing from 64.60 ± 4.65 to 83.08 ± 2.26. Keywords: Code Blue System, Automated External Defibrilator, Nurse